Thermal battery composite positive electrode material with high specific energy and long endurance as well as preparation method and application of thermal battery composite positive electrode material

By mixing high-conductivity cobalt-based binary composite cathode materials A and B to form cobalt-based multi-composite cathode materials, the existing thermal battery cathode materials have been solved, and the demand for high-specific energy and long-term flight time is achieved, and the working time of the battery is extended.

CN119650621APending Publication Date: 2025-03-18GUIZHOU MEILING POWER SUPPLY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411703414.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

In the long-term use of existing thermal battery positive electrode materials, there is a problem of low pyrolysis temperature and low specific energy in long-term use, which is difficult to meet the needs of high-specific energy thermal batteries.

Method used

By mixing the high-conductive cobalt-based binary composite cathode material A and the high-conductive cobalt-based binary composite cathode material B in a certain proportion, a cobalt-based multi-composite cathode material is formed, and a composite cathode material with high pyrolysis temperature, good conductivity and high specific energy is prepared.

Benefits of technology

It achieves the increase in the pyrolysis temperature, the enhancement of conductivity and the increase in specific energy, and is suitable for high-specific energy long-time thermal batteries, extending the working time of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650621A_ABST
    Figure CN119650621A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of thermal batteries, in particular to a high-specific-energy long-endurance thermal battery composite positive electrode material and a preparation method and application thereof.The composite positive electrode material is formed by compounding a high-capacity cobalt-based multi-component composite positive electrode material A and a high-conductivity cobalt-based multi-component composite positive electrode material B. Compared with traditional FeS2 and CoS2 positive electrode materials, the composite positive electrode material has the advantages that the specific energy of the composite positive electrode material is greatly improved; the material has the advantages of high pyrolysis temperature, good conductivity and high specific energy, and is suitable for high-specific-energy long-endurance thermal batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of thermal batteries, and in particular to a composite positive electrode material for a thermal battery with high specific energy and long flight time, and a preparation method and application thereof. Background Art

[0002] Thermal battery is a heat-activated reserve battery. When stored at room temperature, the electrolyte is a non-conductive solid. When used, the heating agent inside is ignited by an activated electric ignition head or a striker mechanism, so that the electrolyte melts and becomes an ion conductor, which is activated. The storage time is theoretically unlimited, and the actual measurable value is more than 17 years. Due to its high output power, small internal resistance, wide operating temperature range, long storage time, rapid and reliable activation, and no maintenance, it has developed into an ideal power source for modern aerospace equipment.

[0003] With the rapid development of electrical equipment, higher and higher requirements are put forward for the use of thermal batteries. In addition to high power output, higher and higher requirements are also put forward for the working time of the battery, which is gradually extended from the initial 10 minutes to 1 hour or even 2 hours. At present, the most widely used positive electrode materials for thermal batteries are FeS2 positive electrode materials and CoS2 positive electrode materials. Among them, the pyrolysis temperature of FeS2 positive electrode material is relatively low, only 550℃. During the operation of the thermal battery, the positive electrode material will undergo pyrolysis, resulting in a large specific energy loss of the positive electrode material, resulting in a low specific energy in the long-flight thermal battery; the pyrolysis temperature of CoS2 positive electrode material is relatively high, reaching 650℃, but its specific energy is relatively small, only 1070As / g, and it is not suitable for long-flight high-specific energy batteries.

[0004] Therefore, finding a positive electrode material with the advantages of high pyrolysis temperature, good electrical conductivity and high specific energy, which is suitable for the application of high specific energy and long-endurance thermal batteries, is the current key research direction. Summary of the invention

[0005] In order to solve the above-mentioned technical problems existing in the prior art, the present invention provides a high-energy-density and long-endurance thermal battery composite positive electrode material and a preparation method and application thereof, which are specifically achieved through the following technical solutions.

[0006] A high-energy-density, long-endurance thermal battery composite positive electrode material is prepared by mixing a high-conductivity cobalt-based binary composite positive electrode material A and a cobalt-based binary composite positive electrode material B.

[0007] Furthermore, the cobalt-based multi-component composite positive electrode material is C coated Co a C b D c S2(a+b+C=1).

[0008] The method for preparing the high specific energy and long flight time thermal battery composite positive electrode material specifically comprises the following steps:

[0009] Step 1: Preparation of high-capacity cobalt-based binary composite positive electrode material A: After mixing cobalt powder and metal powder C evenly, mix them with S powder for a second time, then place them in an ark, push them into the reactor A zone, heat them for 4 to 10 hours under the protection of an inert atmosphere, stir them for a second time, transfer them to the B zone, heat them for another 1 to 2 hours under the protection of an inert atmosphere, and finally transfer them to the C zone. After heating and desulfurization under a certain inert gas flow, transfer them to the D zone and cool them naturally to obtain the high-conductivity cobalt-based binary composite positive electrode material A for standby use;

[0010] Step 2: Preparation of high-conductivity cobalt-based binary composite positive electrode material B: After mixing cobalt powder and metal powder D evenly, mix them with S powder for a second time, then place them in an ark, push them to the reactor A zone and heat them for 4 to 10 hours under the protection of an inert atmosphere, stir them for a second time and transfer them to the B zone, heat them for another 1 to 2 hours under the protection of an inert atmosphere, and finally transfer them to the C zone. After heating and desulfurization under a certain inert gas flow, transfer them to the D zone and cool them naturally to obtain the high-conductivity cobalt-based binary composite positive electrode material B for standby use;

[0011] Step 3: Preparation of cobalt-based multi-component composite positive electrode material: Mix high-conductivity cobalt-based binary composite positive electrode material A and high-conductivity cobalt-based binary composite positive electrode material B in a certain proportion to obtain a cobalt-based multi-component composite positive electrode material pre-product, and then mix it with E material and conductive agent for a second time, and then place it in an ark, push it to the reactor A zone, heat it for 4 to 10 hours, and cool it naturally to obtain a cobalt-based multi-component composite positive electrode material.

[0012] Furthermore, the metal powder C in step 1 is Fe powder or Sn powder.

[0013] Furthermore, the metal powder D in step 1 is Cu powder or Ni powder.

[0014] Furthermore, in step 1 and step 2, the ratio of cobalt powder to metal powder C / D powder is 5:(1-10).

[0015] Furthermore, in the steps 1 and 2, the mixing ratio of the cobalt powder and the metal powder C / D powder to the S source is 1:(2.05-2.4).

[0016] Furthermore, in step 1 and step 2, the heating temperature of zone A is 250°C to 450°C, the heating temperature of zone B is 450°C to 520°C, and the heating temperature of zone C is 550°C to 600°C.

[0017] Furthermore, the air flow rate in zone C is 0.2 / L to 0.5L / min.

[0018] Furthermore, in the step 3, the mixing ratio of the high-conductivity cobalt-based binary composite positive electrode material A and the high-conductivity cobalt-based binary composite positive electrode material B is one of (1-5): (1-5); the mixing ratio of the cobalt-based multi-component composite positive electrode material pre-product with the E material and the conductive agent is 100: (10-25): (1-5).

[0019] Furthermore, in step 3, the heating temperature of zone A is 350°C to 500°C.

[0020] Furthermore, the E material is any one of LiCl-KCl, LiF-LiCl-LiBr, LiF-LiCl-LiBr-LiI, LiF-LiCl-LiBr-CsBr, and LiF-LiCl-LiBr-CsCl halide electrolytes, and the conductive agent is one or more of metal Ag powder, Cu powder, Ni powder, graphene, conductive carbon black, and conductive graphite mixed in any proportion.

[0021] The application of the high specific energy and long flight time thermal battery composite positive electrode material in thermal batteries.

[0022] Furthermore, the thermal battery is an application of long-flight thermal batteries.

[0023] The composite positive electrode material obtained in the present application is composed of a high-capacity cobalt-based multi-component composite positive electrode material A and a high-conductivity cobalt-based multi-component composite positive electrode material B. Compared with traditional FeS2 and CoS2 positive electrode materials, the composite positive electrode material has the advantages of high pyrolysis temperature, good electrical conductivity and high specific energy, and is suitable for high specific energy and long-endurance thermal battery applications.

[0024] Compared with the prior art, the technical effects created by the present invention are embodied in:

[0025] The main phase of the pyrolysis-resistant cobalt-based multi-component composite positive electrode material of the present invention is composed of pyrolysis-resistant Co x Fe / Sn 1-x S2 composite cathode material and pyrolysis-resistant Co x Ni / Cu 1-x The CoS2 composite positive electrode material is a composite of FeS2 and SnS2 positive electrode materials, among which FeS2 and SnS2 positive electrode materials have high capacity, but low pyrolysis temperature and large internal resistance of the product, which limits their application in long-endurance thermal batteries. Preliminary tests have shown that the doping of Co phase can increase the pyrolysis temperature of the composite material. However, as the discharge of CoS2 positive electrode material proceeds, the internal resistance of the product is large, and its own internal resistance will gradually increase, which is not suitable for the application of long-endurance thermal batteries. To further solve this problem, the CoS2 positive electrode material with the same pyrolysis resistance and high conductivity was prepared. x Ni / Cu 1-xS2 composite positive electrode material, the latter's product elemental Ni and Cu have good conductivity, which makes up for the influence of the large internal resistance of the later product of CoS2 product, so that the composite positive electrode material has better power output and the specific energy of the battery is further improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 TG curves of the single-phase positive electrode material and the composite positive electrode material prepared in this application.

[0027] Figure 2 The discharge curves of the single-phase positive electrode material and the composite positive electrode material prepared in this application. DETAILED DESCRIPTION

[0028] The technical solution of the present invention is further defined below in conjunction with specific implementation methods, but the scope of protection required is not limited to the description.

[0029] Example 1

[0030] Step 1: Preparation of high-capacity cobalt-based binary composite positive electrode material A: After cobalt powder and metal powder Fe are evenly mixed in a ratio of 1:1, they are mixed with S powder in a ratio of 1:2.05 for a second time, then placed in an ark, pushed into the reactor A zone, heated to 250°C, heated for 4 hours under an inert atmosphere, and transferred to the B zone after secondary stirring, heated to 450°C, heated for another 1 hour under an inert atmosphere (airflow rate 0.2 / L / min), and finally transferred to the C zone, heated to 550°C, heated and desulfurized under a certain inert airflow (airflow rate 0.5 / L / min), and then transferred to the D zone (normal temperature) for natural cooling to obtain a high-conductivity cobalt-based binary composite positive electrode material A for standby use;

[0031] Step 2: Preparation of high-conductivity cobalt-based binary composite positive electrode material B: After cobalt powder and metal powder Ni powder are evenly mixed in a ratio of 1:1, they are mixed again with S powder in a ratio of 1:2.05, and then placed in an ark and pushed to the reactor A zone, heated to 250°C, heated for 4 hours under the protection of a medium inert atmosphere, and then stirred for a second time and transferred to the B zone, heated to 450°C, and heated for another 1 hour under the protection of an inert atmosphere (airflow rate 0.2 / L / min), and finally transferred to the C zone, heated to 550°C, heated and desulfurized under a certain inert airflow (airflow rate 0.5 / L / min), and then transferred to the D zone (room temperature) for natural cooling to obtain a high-conductivity cobalt-based binary composite positive electrode material B for standby use;

[0032] Step 3: Preparation of cobalt-based multi-component composite positive electrode material: Mix high-conductivity cobalt-based binary composite positive electrode material A and high-conductivity cobalt-based binary composite positive electrode material B in a ratio of 1:1 to obtain a cobalt-based multi-component composite positive electrode material pre-product, and then mix it with LiF-LiCl-LiBr-CsBr E material and graphene in a ratio of 100:20:2 for a second time, then place it in an ark, push it to the reactor A zone, heat it to 350°C, heat it for 4 hours, and cool it naturally to obtain a cobalt-based multi-component composite positive electrode material.

[0033] The high conductivity and pyrolysis-resistant Co x Fe y Ni z S2 (x+y+z=1) material is used as the positive electrode of the thermal battery, LiF-LiCl-KBr electrolyte doped with MgO is used as the separator, LiB is used as the negative electrode, Fe powder doped with KClO4 is used as the heating powder, and a monomer sheet with a diameter of 82 mm is prepared. 16 monomers are connected in series as one stack, and 2 stacks are connected in parallel to form a unit battery (similarly, Co m Fe n The positive electrode powder of S2 (m+n=1) was assembled into a unit thermal battery in the same way as a control sample), and the unit battery was discharged at a constant current of 10A. Figure 2 It can be seen that the positive electrode material unit battery prepared in this application has a higher working voltage under the same time. In practical application, if the working voltage is cut off at the lower limit, it has a longer working time and is suitable for long-duration thermal batteries. Figure 1 It can be seen from the thermogravimetric curves of the two positive electrode materials that the composite positive electrode of the present application has a higher pyrolysis temperature.

[0034] Finally, it should be pointed out that the above embodiments are only representative examples of the present invention. Obviously, the technical solution of the present invention is not limited to the above embodiments, and there are many variations. All variations that can be directly derived or associated with the content disclosed by ordinary technicians in this field should be considered as the protection scope of the present invention.

Claims

1. A high specific energy and long flight time thermal battery composite positive electrode material, characterized in that: It is a mixture of high-conductivity cobalt-based binary composite positive electrode material A and cobalt-based binary composite positive electrode material B.

2. The high specific energy and long flight time thermal battery composite positive electrode material according to claim 1, characterized in that: The cobalt-based multi-component composite positive electrode material is C coated with Co a C b D c S2(a+b+C=1).

3. The method for preparing the high specific energy and long flight time thermal battery composite positive electrode material according to claim 1, characterized in that: The specific steps include: Step 1: Preparation of high-capacity cobalt-based binary composite positive electrode material A: After mixing cobalt powder and metal powder C evenly, mix them with S powder for a second time, then place them in an ark, push them into the reactor A zone, heat them for 4 to 10 hours under the protection of an inert atmosphere, stir them for a second time, transfer them to the B zone, heat them for another 1 to 2 hours under the protection of an inert atmosphere, and finally transfer them to the C zone. After heating and desulfurization under a certain inert gas flow, transfer them to the D zone and cool them naturally to obtain the high-conductivity cobalt-based binary composite positive electrode material A for standby use; Step 2: Preparation of high-conductivity cobalt-based binary composite positive electrode material B: After mixing cobalt powder and metal powder D evenly, mix them with S powder for a second time, then place them in an ark, push them to the reactor A zone and heat them for 4 to 10 hours under the protection of an inert atmosphere, stir them for a second time and transfer them to the B zone, heat them for another 1 to 2 hours under the protection of an inert atmosphere, and finally transfer them to the C zone. After heating and desulfurization under a certain inert gas flow, transfer them to the D zone and cool them naturally to obtain the high-conductivity cobalt-based binary composite positive electrode material B for standby use; Step 3: Preparation of cobalt-based multi-component composite positive electrode material: After uniformly mixing high-conductivity cobalt-based binary composite positive electrode material A and high-conductivity cobalt-based binary composite positive electrode material B, a cobalt-based multi-component composite positive electrode material pre-product is obtained, which is then mixed with E material and a conductive agent for a second time, and then placed in an ark, pushed into zone A of the reactor, heated for 4 to 10 hours, and then naturally cooled to obtain a cobalt-based multi-component composite positive electrode material.

4. The method for preparing a composite positive electrode material for a high specific energy and long flight time thermal battery according to claim 1, characterized in that: The metal powder C described in step 1 is Fe powder or Sn powder.

5. The method for preparing a composite positive electrode material for a high specific energy and long flight time thermal battery according to claim 1, characterized in that: The metal powder D described in step 1 is Cu powder or Ni powder.

6. The method for preparing a composite positive electrode material for a high specific energy and long flight time thermal battery according to claim 1, characterized in that: In the steps 1 and 2, the ratio of cobalt powder to metal powder C / D powder is 5:(1-10).

7. The method for preparing a composite positive electrode material for a high specific energy and long flight time thermal battery according to claim 1, characterized in that: In the steps 1 and 2, the mixing ratio of the cobalt powder and the metal powder C / D powder to the S source is 1:(2.05-2.4).

8. The method for preparing a composite positive electrode material for a high specific energy and long flight time thermal battery according to claim 1, characterized in that: In the steps 1 and 2, the heating temperature of zone A is 250°C to 450°C, the heating temperature of zone B is 450°C to 520°C, and the heating temperature of zone C is 550°C to 600°C.

9. Application of the high specific energy and long flight time thermal battery composite positive electrode material according to claim 1 in thermal batteries.

10. The use according to claim 9, characterized in that: The thermal battery aspect is the application of long-flight thermal batteries.